Nanofiber film of LM and carbon nanotube composite filler and preparation method of nanofiber film
By introducing LM@CNT filler and PEDOT:PSS into the TPU, and using electrospinning technology to prepare LM@CNT/PEDOT:PSS/TPU nanofiber films, the problems of improved dispersion stability and dielectric performance of liquid metals in composite materials are solved, and a capacitive sensor with high sensitivity and fast response are achieved.
Patent Information
- Application Number
- CN202510093433.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-21
AI Technical Summary
In the prior art, when preparing PVDF-HFP fiber films containing liquid metals, the effect of liquid metals to increase the dielectric constant of the film during electrospinning is not ideal, and problems such as the dispersion stability of liquid metals in composite materials and the formation of oxide layers need to be further studied and solved.
The nanofiber film preparation method is adopted to prepare LM@CNT filler by grinding, and the filler and PEDOT:PSS are introduced into the TPU, and the LM@CNT/PEDOT:PSS/TPU nanofiber film is prepared by electrospinning technology.
It significantly improves the dielectric constant and relative capacitance change of capacitive sensors, improves the sensitivity and response speed of the sensor, and maintains stability under high voltage, and is suitable for applications such as human motion monitoring.
Smart Images

Figure CN119900106A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flexible electronic devices, and in particular to a nanofiber film of LM and carbon nanotube composite filler and a preparation method thereof. Background Art
[0002] With the continuous advancement of artificial intelligence technology, wearable electronic devices have become a hot topic in both scientific research and the market, especially in the fields of artificial electronic skin, medical monitoring and intelligent robots. As a key component of wearable devices, flexible capacitive pressure sensors have been widely used in human motion monitoring and physiological signal tracking due to their high sensitivity, fast response, wide response range and excellent stability. However, the design and development of capacitive pressure sensors with both high sensitivity and wide response range is still an important challenge facing this field.
[0003] The working principle of capacitive pressure sensors is based on the change in the distance between the plates or the dielectric constant when under pressure, resulting in a corresponding change in the capacitance value. The ideal dielectric layer material must have the following characteristics: maintain structural stability and dielectric properties under high pressure to ensure capacitance continuity; at the same time, show significant capacitance response to small pressure changes to achieve high-precision monitoring. In order to improve the sensitivity of the sensor, researchers have tried to add conductive fillers to polymers to increase the dielectric constant. For example, Yang et al. significantly improved the dielectric constant and sensor sensitivity by adding carbon nanotubes to PVDF. However, the introduction of carbon-based materials also brings about the problems of decreased elastic modulus and reduced compressibility of the sensor, which limits the further improvement of sensor performance.
[0004] In recent years, conductive liquid fillers, especially ionic fluids and liquid metals (LM), have become a new research hotspot because they can give polymers conductivity without making the base material embrittled. The prior art discloses the use of sugar particle templates to make porous structures, adding liquid metal to Ecoflex, and preparing a dielectric layer with excellent pressure sensitivity, while improving the dielectric constant and compressibility. This shows that liquid metal has significant advantages in improving the elastic modulus of the matrix material. However, when preparing PVDF-HFP fiber films containing liquid metal, it was found that the effect of liquid metal on the dielectric constant of the film during electrospinning was not ideal.
[0005] The dielectric properties of liquid metal in a soft matrix are restricted by many factors, including the insulating properties of the surfactant used to disperse the liquid metal, the oxide shell (such as Ga2O3) formed by the oxidation of the liquid metal in the air, etc. These factors will have an adverse effect on the electrical properties of liquid metal polymer composites. To solve these problems, a mixed filler strategy came into being. In addition, the prior art also adds CNT / LM composites to polydimethylsiloxane (PDMS), and the resulting composite film exhibits good electrical conductivity. The combination of CNT and LM not only exhibits unique mechanical, electrical, magnetic and thermal properties, but also utilizes the fluid properties of LM and the rigidity of CNT to solve the entanglement structure formed by van der Waals forces between carbon nanotubes and the difficulty in preparing composite materials caused by the incompatibility of LM with non-metallic materials. In addition, the prior art also discloses a stretchable composite film composed of PEDOT:PSS and reduced graphene oxide (r-GO). By adding PEDOT:PSS, a strain capacity of more than 200% of the polymer film is achieved.
[0006] Although liquid metal has significant potential in improving the performance of capacitive pressure sensors, issues such as its dispersion stability in composite materials, the formation of oxide layers, and compatibility with other materials still need further research and resolution. Therefore, developing a stable liquid metal dispersion technology and optimizing the structure of composite materials are of great significance for improving the comprehensive performance of capacitive pressure sensors. Summary of the invention
[0007] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a nanofiber film of LM and carbon nanotube composite filler and a preparation method thereof. The prepared LM@CNT / PEDOT:PSS / TPU nanofiber film improves the performance of capacitive sensors, optimizes the preparation process, and expands its application in the field of flexible sensors for human motion monitoring, etc.
[0008] To achieve the above object, the present invention provides the following solutions:
[0009] A method for preparing a nanofiber film of LM and carbon nanotube composite filler comprises the following steps:
[0010] S1. Weigh the raw materials THF, DMF, TPU, LM, CNT, and PEDOT:PSS, mix THF and DMF in a ratio of 1:1 to form a base solvent, and grind LM and CNT to prepare LM@CNT filler;
[0011] S2, the base solvent is divided into two parts, A and B, in a ratio of 6:4; the A part is used to dissolve TPU to prepare a component A solution, and the B part is added with the LM@CNT filler and the PEDOT:PSS, and is subjected to ultrasonic and mechanical stirring to prepare a component B solution;
[0012] S3. Slowly drop the B component solution into the A component solution under stirring, and continue stirring to allow the various components to fully mix and react to form a LM@CNT / PEDOT:PSS / TPU spinning solution with uniform composition, stable performance and suitable for spinning;
[0013] S4. Prepare a LM@CNT / PEDOT:PSS / TPU nanofiber film by electrospinning the LM@CNT / PEDOT:PSS / TPU spinning solution.
[0014] Preferably, in step S1, the usage ratio of TPU:THF:DMF:CNT:LM:PEDOT:PSS solution is (2-2.5) g:(5-7) mL:(5-7) mL:(10-11) mg:(0.1-0.3) g:(0.05-0.15) g.
[0015] Preferably, in step S1, the preparation process of the LM@CNT filler is specifically as follows: adding 0.1-0.3 g of LM to 10-11 mg of carbon nanotubes CNT, grinding for 0.5-1 h until the mixture is uniformly mixed, and the grinding particle size is 5-20 um, thereby obtaining the LM@CNT filler.
[0016] Preferably, in step S2, the preparation process of the component A solution is specifically as follows: 6 to 8.5 ml of the base solvent A is added to a reagent bottle, then 2 to 2.5 g of TPU is added to the reagent bottle, and the reagent bottle is placed on a heating table and gradually heated to 55 to 65° C., then heated for 0.45 to 1 h until it is evenly dispersed, and finally the mixture is cooled to room temperature 24 to 28° C. and there are no bubbles in the bottle to obtain the component A solution.
[0017] Preferably, in step S2, the preparation process of the component B solution is specifically as follows: 0.3-0.7 g of LM@CNT and 0.05-0.15 g of PEDOT:PSS are added to 4-5.5 ml of the component B base solvent, and then mechanically stirred at a speed of 20-30 rpm for 3-6 minutes in a water bath at 24-28°C and 60 Hz supermagnetic dispersion to obtain a component B solution.
[0018] Preferably, in step S3, the preparation process of the LM@CNT / PEDOT:PSS / TPU spinning solution is specifically as follows: a reagent bottle containing the component A solution is clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 600-800 r / min, and then the component B solution is added dropwise to the component A solution and mechanically stirred at a speed of 1000-1200 rpm for 30-60 minutes to obtain the LM@CNT / PEDOT:PSS / TPU spinning solution.
[0019] Preferably, in step S4, the preparation process of the LM@CNT / PEDOT:PSS / TPU nanofiber film is specifically as follows: the LM@CNT / PEDOT:PSS / TPU spinning solution is loaded into an electrospinning device, and spinning is performed at a feed rate of 4 to 5 mL / h at a voltage of 15 to 20 kV; then a rotating drum with an aluminum foil-covered surface and a speed control function is used as a collector, and its speed is set to 200 to 300 r / min, and a negative voltage of 1 kV is connected to the collector; at the same time, the distance between the spinning needle and the collector is maintained at 10 to 15 cm; after a spinning process of 4 to 7 hours, the nanocomposite fiber is gradually deposited on the aluminum foil, and finally the LM@CNT / PEDOT:PSS / TPU nanofiber film is formed.
[0020] Preferably, the dielectric constant of the LM@CNT / PEDOT:PSS / TPU nanofiber film is 8.63-24.8, the tensile strength is 2.19-3.42 MPa, and the elongation at break is 152.6%-279.6%.
[0021] Another object of the present invention is to provide a LM@CNT / PEDOT:PSS / TPU nanofiber film prepared by the above-mentioned method for preparing a nanofiber film of LM and carbon nanotube composite filler.
[0022] Another object of the present invention is to provide an application of the above-mentioned LM@CNT / PEDOT:PSS / TPU nanofiber film in a flexible sensor. The capacitive sensor prepared by the LM@CNT / PEDOT:PSS / TPU nanofiber film maintains GF=1.07~3.214 within the pressure range of 0.1-20KPa, and the response time is 20~22ms; the sensitive performance maintains stable output after 3000 cycles.
[0023] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0024] (1) The present invention effectively solves the problem of poor toughness of liquid metal and other composite materials in electrospinning. By adding conductive fillers LM@CNT and PEDOT:PSS to the polyurethane film, the dielectric constant of the film is significantly improved. This makes the capacitive sensor with LM@CNT / PEDOT:PSS / TPU nanofiber film as the dielectric layer have a higher initial capacitance value and a large relative capacitance change. The sensor exhibits high sensitivity, with a sensitivity of up to 3.214 kPa in the linear range of 0 to 5 kPa. -1 , 1.07 kPa in the linear range of 5 to 20 kPa -1; Wide detection range, up to 0 ~ 1000kPa; extremely fast response speed, response time is less than 20ms; good stability, after 3000 cycles under 5kPa pressure, the sensitive performance is still stable output. These excellent properties make the sensor have great application value in the fields of human motion monitoring and physiological signal tracking.
[0025] (2) The preparation method provided by the present invention is simple and easy to operate, has broad requirements for the experimental environment, and does not require special and complex experimental conditions, which provides convenience for the promotion and application of the technology. During the experiment, the use of toxic reagents is minimized, the pollution to the environment is reduced, and it is in line with the concept of green chemistry. This environmentally friendly and easy-to-operate preparation process is not only conducive to scientific research personnel in the laboratory, but also lays the foundation for large-scale industrial production.
[0026] (3) The LM@CNT / PEDOT:PSS / TPU fiber film prepared by the present invention has a wide range of application prospects in the field of flexible sensors. The flexible pressure sensor assembled from it can realize a wide range of human motion monitoring, such as accurately capturing the dynamic response signals of biceps activity and finger clicking on the mouse. It can also be used for vocal cord pressure testing, by detecting the local pressure changes caused by vocal cord vibration and converting them into capacitance signals, and then analyzing the capacitance changes corresponding to different words, showing high response ability and resolution under low detection pressure, that is, small vibration feedback, and playing an important role in the field of wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 This is a flow chart of a method for preparing a nanofiber film of LM and carbon nanotube composite filler of the present invention;
[0029] Figure 2 This is an experimental flow chart of a method for preparing a nanofiber film of LM and carbon nanotube composite filler of the present invention;
[0030] Figure 3 The test diagrams of the LM@CNT / PEDOT:PSS / TPU nanofiber films provided by the present invention; wherein, Figure 3 (a) is the surface structure diagram of the prepared TPU. Figure 3 (b) is the surface structure diagram of the prepared LM@CNT / PEDOT / TPU nanofiber film. Figure 3(c) is the cross-sectional SEM image of LM@CNT / PEDOT / TPU nanofiber film. Figure 3 (d), (e) and (f) are the fiber cross-section images and EDS spectra at higher magnifications, respectively. Figure 3 (g) is the XRD test result of CNT and LM@CNT fillers. Figure 3 (h) is the infrared spectra of TPU and LM@CNT / PEDOT / TPU nanofiber films. Figure 3 (i) is the stress-strain curve of pure TPU and TPU electrospun fibers filled with CNT, PEDOT:PSS, and LM@CNT;
[0031] Figure 4 The dielectric performance test diagrams of the LM@CNT / PEDOT:PSS / TPU nanofiber films provided by the present invention and the performance diagrams of the prepared sensors; Figure 4 (a) is a comparison of the relative dielectric constant and dielectric loss of LM@CNT / TPUP composite nanofiber films with different addition ratios. Figure 4 (b) is a comparison of the relative dielectric constant and dielectric loss of LM@CNT / TPUP composite nanofiber films with different addition concentrations. Figure 4 (c) is a comparison chart of the relative dielectric constant and dielectric loss of fiber films with different conductive fillers. Figure 4 (d) is a comparison of the sensing performance of LM@CNT / TPUP composite nanofiber films with different addition ratios. Figure 4 (e) is a comparison chart of sensor performance of LM@CNT / PEDOT / TPU composite nanofiber films with the same added concentration. Figure 4 (f) is a graph showing the change in initial capacitance and sensitivity of the sensor when the weight percentage changes from 0 to 25%.
[0032] Figure 5 This is a comparison chart of the comprehensive performance of the LM@CNT / PEDOT / TPU composite nanofiber film sensor prepared by the present invention and the sensor in the prior art; wherein, Figure 5 (a) is the dynamic response diagram of ΔC / C0 under cyclic loading and unloading pressures of 20, 40, 60 and 100 kPa. Figure 5 (b) is the relative change of the capacitance of the sensor under the step loading / unloading pressure of 2.5kPa~20kPa. Figure 5 (c) is a schematic diagram of the hysteresis rate of the sensor in continuous loading and unloading cycles. Figure 5 (d) is a schematic diagram of the response time and recovery time of the sensor under a pressure of 25Pa. Figure 5(e) is the response diagram of ΔC / C0 under 5 kPa pressure and repeated loading-unloading for 3000 cycles. Figure 5 (f) is a comparison chart of the maximum sensitivity detection range of the present invention, the existing electrospinning dielectric layer sensor and two microstructure sensors;
[0033] Figure 6 A fast-response, skin-adhesive flexible pressure sensor assembled from the LM@CNT / PEDOT / TPU composite nanofiber film provided by the present invention is used for monitoring human motion over a wide range; wherein: Figure 6 (a) is a schematic diagram of the change of ΔC / C0 when stimulating the biceps brachii. Figure 6 (b) is a schematic diagram of the change of ΔC / C0 when the finger presses the mouse at different speeds. Figure 6 (c) is the flow chart of vocal cord pressure test. Figure 6 (d) in the figure is the Gram graph corresponding to congratulation, consistent, contact, where, are, and you. Figure 6 (e) is a schematic diagram of the ΔC / C0 changes corresponding to congratulation, consistent, contact, where, are, and you. Figure 6 (f) in the figure is the performance graph of the indicators on the test set and the validation set. Figure 6 (g) in the figure is the confusion matrix of the grid's diagnosis results for word capacitance change data;
[0034] Figure 7 This is a comparison diagram of the static conditions of CNT and CNT@LM provided by the present invention after being uniformly dispersed in THF / DMF solvent. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] The present invention provides a method and application for preparing LM@CNT / PEDOT:PSS / TPU fiber film by one-step method. LM@CNT is prepared by grinding. Thermoplastic polyurethane (TPU) is used as a substrate, carbon nanotubes (MWCNTs) and liquid metal (LM) composite fillers (LM@CNT) obtained by a simple grinding method and trace poly (3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) are introduced into the TPU fiber to form a conductive network, and a LM@CNT / PEDOT:PSS / TPU high dielectric constant fiber film is obtained. The nanofibers of the LM@CNT / PEDOT / TPU composite material present a randomly oriented structure and the fiber diameters vary greatly. According to the statistics of fiber diameter, the average diameter of the original nanofiber is 0.21μm, and the average diameter of the composite nanofiber is 0.44μm. The surface of the polyurethane fiber with filler has many uneven protrusions. The present invention uses CNT to modify the surface of LM droplets, which not only improves the dispersion stability of LM in the solvent, but also improves the serious sedimentation and uneven dispersion problems caused by the high density difference between LM and the composite material during the curing process. And by introducing LM@CNT in TPU, the dielectric properties of the fiber film are improved, and by introducing PEDOT:PSS, the problem that liquid metal is difficult to use for electrospinning after being compounded with other materials is solved. Specifically, Figure 1 and Figure 2 As shown, the present invention provides a method for preparing a nanofiber film of LM and carbon nanotube composite filler, comprising the following steps:
[0038] S1. Weigh the raw materials THF, DMF, TPU, LM, CNT, and PEDOT:PSS, mix THF and DMF in a ratio of 1:1 to form a base solvent, and grind LM and CNT to prepare LM@CNT filler;
[0039] S2, the base solvent is divided into two parts, A and B, in a ratio of 6:4; the A part is used to dissolve TPU to prepare a component A solution, and the B part is added with the LM@CNT filler and the PEDOT:PSS, and is subjected to ultrasonic and mechanical stirring to prepare a component B solution;
[0040] S3. Slowly drop the B component solution into the A component solution under stirring, and continue stirring to allow the various components to fully mix and react to form a LM@CNT / PEDOT:PSS / TPU spinning solution with uniform composition, stable performance and suitable for spinning;
[0041] S4. Prepare a LM@CNT / PEDOT:PSS / TPU nanofiber film by electrospinning the LM@CNT / PEDOT:PSS / TPU spinning solution.
[0042] In step S1, the dosage ratio of TPU:THF:DMF:CNT:LM:PEDOT:PSS solution is (2-2.5) g:(5-7) mL:(5-7) mL:(10-11) mg:(0.1-0.3) g:(0.05-0.15) g. The preparation process of the LM@CNT filler is as follows: add 0.1-0.3 g of LM to 10-11 mg of carbon nanotubes CNT, grind for 0.5-1 h until the mixture is evenly mixed, and grind the particle size to 5-20 um, thereby obtaining the LM@CNT filler.
[0043] In step S2, the preparation process of the component A solution is specifically as follows: 6-8.5 ml of the component A base solvent is added to a reagent bottle, then 2-2.5 g of TPU is added to the reagent bottle, and the reagent bottle is placed on a heating table and gradually heated to 55-65°C, then heated for 0.45-1h until uniformly dispersed, and finally the mixture is cooled to room temperature 24-28°C and there are no bubbles in the bottle to obtain the component A solution. The preparation process of the component B solution is specifically as follows: 0.3-0.7 g of LM@CNT and 0.05-0.15 g of PEDOT:PSS are added to 4-5.5 ml of the component B base solvent, and then mechanically stirred at a speed of 20-30 rpm for 3-6 minutes in a water bath at 24-28°C and supermagnetically dispersed at 60 Hz to obtain the component B solution.
[0044] In step S3, the preparation process of the LM@CNT / PEDOT:PSS / TPU spinning solution is specifically as follows: a reagent bottle containing the component A solution is clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 600 to 800 r / min, and then the component B solution is added dropwise to the component A solution and mechanically stirred at a speed of 1000 to 1200 rpm for 30 to 60 minutes to obtain the LM@CNT / PEDOT:PSS / TPU spinning solution.
[0045] In step S4, the preparation process of the LM@CNT / PEDOT:PSS / TPU nanofiber film is specifically as follows: the LM@CNT / PEDOT:PSS / TPU spinning solution is loaded into an electrospinning device, and spinning is performed at a feed rate of 4-5 mL / h at a voltage of 15-20 kV; then a rotating drum with a surface covered with aluminum foil and a speed control function is used as a collector, and its speed is set to 200-300 r / min, and a negative voltage of 1 kV is connected to the collector; at the same time, the distance between the spinning needle and the collector is maintained at 10-15 cm; after a spinning process of 4-7 hours, the nanocomposite fiber is gradually deposited on the aluminum foil, and finally the LM@CNT / PEDOT:PSS / TPU nanofiber film is formed.
[0046] The LM@CNT / PEDOT:PSS / TPU nanofiber film prepared by the above method has a dielectric constant of 8.63-24.8, a tensile strength of 2.19-3.42 MPa, and an elongation at break of 152.6%-279.6%.
[0047] Example 1
[0048] In this embodiment, a method for preparing a LM@CNT / PEDOT:PSS / TPU nanofiber film comprises:
[0049] 2g of TPU was dissolved in 6mL of THF / DMF solution, and then mechanically stirred at 600rpm for 45min at 60℃ to obtain TPU solution. 0.15g of LM@CNT and 0.75g of PEDOT:PSS were added to 4mL of THF / DMF solution, placed in a 25℃ water bath and mechanically stirred at 20rpm for 3min at 60Hz supermagnetic dispersion to obtain a conductive filler dispersion solution. The TPU solution reagent bottle was clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 700r / min, and the conductive dispersion solution was dripped into the TPU solution and mechanically stirred at 1000rpm for 45min. Electrospinning was performed at 18kV at a feed rate of 4.8mL / h. A rotating drum covered with aluminum foil with a speed control function was used as a collector, with a speed of 300r / min and a negative voltage of 1kV. The distance between the needle and the collector was 15cm. The nanocomposite fibers were collected on aluminum foil and spun for 7 h to obtain LM@CNT / PEDOT:PSS / TPU nanofiber films.
[0050] Example 2
[0051] In this embodiment, a method for preparing a LM@CNT / PEDOT:PSS / TPU nanofiber film includes:
[0052] 2g of TPU was dissolved in 6mL of THF / DMF solution, and then mechanically stirred at 600rpm for 45min at 60℃ to obtain TPU solution. 0.2g of LM@CNT and 0.1g of PEDOT:PSS were added to 4mL of THF / DMF solution, placed in a 25℃ water bath and mechanically stirred at 20rpm for 3min at 60Hz supermagnetic dispersion to obtain a conductive filler dispersion solution. The TPU solution reagent bottle was clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 700r / min, and the conductive dispersion solution was dropped into the TPU solution and mechanically stirred at 1000rpm for 45min. Electrospinning was performed at 18kV at a feed rate of 4.8mL / h. A rotating drum covered with aluminum foil with a speed control function was used as a collector, with a speed of 300r / min and a negative voltage of 1kV. The distance between the needle and the collector was 15cm. The nanocomposite fibers were collected on aluminum foil and spun for 7 h to obtain LM@CNT / PEDOT:PSS / TPU fiber films.
[0053] Example 3
[0054] In this embodiment, a method for preparing a LM@CNT / PEDOT:PSS / TPU nanofiber film comprises:
[0055] 2g of TPU was dissolved in 6mL of THF / DMF solution, and then mechanically stirred at 600rpm for 45min at 60℃ to obtain TPU solution. 0.25g of LM@CNT and 0.125g of PEDOT:PSS were added to 4mL of THF / DMF solution, placed in a 25℃ water bath and mechanically stirred at 20rpm for 3min at 60Hz supermagnetic dispersion to obtain a conductive filler dispersion solution. The TPU solution reagent bottle was clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 700r / min, and the conductive dispersion solution was added dropwise to the TPU solution and mechanically stirred at 1000rpm for 45min. Electrospinning was performed at a feed rate of 4.8mL / h at 18kV. A rotating drum covered with aluminum foil with a speed control function was used as a collector, with a speed of 300r / min and a negative voltage of 1kV connected. The distance between the needle and the collector was 15cm. The nanocomposite fibers were collected on aluminum foil and spun for 7 h to obtain LM@CNT / PEDOT:PSS / TPU nanofiber films.
[0056] Example 4
[0057] In this embodiment, a method for preparing a LM@CNT / PEDOT:PSS / TPU nanofiber film includes:
[0058] 2g of TPU was dissolved in 6mL of THF / DMF solution, and then mechanically stirred at 600rpm for 45min at 60℃ to obtain TPU solution. 0.3g of LM@CNT and 0.15g of PEDOT:PSS were added to 4mL of THF / DMF solution, placed in a 25℃ water bath and mechanically stirred at 20rpm for 3min at 60Hz supermagnetic dispersion to obtain a conductive filler dispersion solution. The TPU solution reagent bottle was clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 700r / min, and the conductive dispersion solution was added dropwise to the TPU solution. The solution was mechanically stirred at 1000rpm for 45min. Electrospinning was performed at 18kV at a feed rate of 4.8mL / h. A rotating drum covered with aluminum foil with a speed control function was used as a collector, with a speed of 300r / min and a negative voltage of 1kV. The distance between the needle and the collector was 15cm. The nanocomposite fibers were collected on aluminum foil and spun for 7 h to obtain LM@CNT / PEDOT:PSS / TPU nanofiber films.
[0059] Comparative Example 1
[0060] The difference from Example 1 is that no liquid metal and PEDOT are added. Other steps are the same as Example 1 to obtain a CNT / TPU fiber film.
[0061] Comparative Example 2
[0062] The difference from Example 1 is that no liquid metal and CNT are added. Other steps are the same as Example 1 to obtain a PEDOT / TPU fiber film.
[0063] Based on the above, the morphology and structure of the original and conductive filler-added polyurethane electrospun samples were analyzed in detail by scanning electron microscopy (SEM). Figure 3 As shown in (a) of the figure, the unfilled polyurethane spinning fibers are evenly distributed without obvious uneven thickness or breakage, which indicates that the electrospinning process is stable and well controlled. Figure 3As shown in (b), the nanofibers of the LM@CNT / PEDOT / TPU composite material present a randomly oriented structure and the fiber diameters vary greatly. According to the statistics of the fiber diameters, the average diameter of the original nanofibers is 0.21μm, and the average diameter of the composite nanofibers is 0.44μm. The addition of LM@CNT can increase the average diameter of the TPU nanofibers. Compared with pure polyurethane fibers, the surface of the polyurethane fibers with fillers has many uneven protrusions. This is because when the size of LM@CNT is larger than the fiber diameter, the fiber surface will protrude. This protrusion makes the film form an irregular secondary structure, which is beneficial to improve the compressibility of the dielectric layer. The irregular structure causes the film thickness to change in a gradient, which is beneficial to the subsequent sensing test of the LM@CNT / PEDOT / TPU sensor. The relative capacitance changes linearly with the application of pressure, thereby providing stability and reliability.
[0064] The fiber cross-sections of TPU and LM@CNT / PEDOT / TPU films were obtained by liquid nitrogen brittle fracture, such as Figure 3 As shown in (c), from the cross section we can see that LM@CNT is evenly distributed in the film. This structure lays the foundation for the good performance of the sensor. Figure 3 (d), (e) and (f) in the figure show the transverse and longitudinal cross-sections and EDS spectra of the film fibers with TPU and LM@CNT added at 250,000 times. It can be seen intuitively that the LM@CNT filler is introduced into the spun fiber. The EDS spectra confirm that the fillers embedded in the fiber are composed of three elements: C, Ga and In. These fillers are evenly distributed in the fiber and are tightly combined with the fiber matrix without obvious agglomeration or separation.
[0065] The successful assembly between LM@CNTs was confirmed by XRD analysis. Figure 3 As shown in (g), after grinding the carbon nanotubes and LM together, the characteristic peaks changed from two to one, among which the characteristic peak of Ga corresponds to 37.715, indicating that the carbon nanotubes are wrapped by liquid metal and tightly bound. The FTIR spectrum records 400cm -1 ~4000cm -1 Spectra in the range, such as Figure 3 As shown in (h), no other new bands appeared after CNT@LM and PEDOT were embedded in TPU nanofibers. The results show that CNT@LM and PEDOT dispersed in nanofibers did not form a new phase. Figure 3(i) Compared with pure TPU fiber membrane, the simple addition of carbon tubes will reduce the tensile elongation at break of the membrane from 213.5% to 152.6%, and increase the tensile strength from 2.19MPa to 3.07MPa. The tensile strength of LM@CNT / PEDOT / TPU fiber membrane is 3.43MPa, and the elongation at break is 288.1%, while the elongation at break of PEDOT / TPU fiber film is 279.6%.
[0066] Reference Figure 4 In (a), (b) and (c), the present invention first prepares composite nanofiber membranes with three different ratios of 15:1, 20:1, and 25:1 at a concentration of 15wt%, and then Figure 4 In (a), we can see that the dielectric constants corresponding to the three ratios are 8.63, 9.71, and 10.52, respectively. When the addition content of LM@CNT is 15wt%, 20wt%, and 25wt%, the dielectric constants corresponding to the LM@CNT / TPUP nanofiber membrane are 10.52, 15.5, and 24.8, respectively. With the increase of LM@CNT concentration, the steady growth of the dielectric constant in the composite film can be attributed to the enhancement of the interface polarization mechanism and the intensification of the Maxwell-Wagner-Sillars (MWS) effect, both of which promote the change of the charge distribution and polarization behavior inside the film. The dielectric constant of the pure TPU fiber film is 6.5, and the dielectric constant has been significantly improved by 6 times after adjusting the filler concentration.
[0067] like Figure 4 As shown in (d), the increase in the proportion of liquid metal increases the dielectric constant. At low concentrations, the change in the internal proportion of the composite filler has little effect on the relative change in sensor capacitance. The sensor sensitivity corresponding to the maximum ratio of 25:1 is 1.55 kPa. -1 (0~5kPa), which is 8 times higher than that of the sensor without filler. Figure 4 As shown in (e), the LM@CNT filler ratio is fixed at 25:1 and the concentration is increased. As the LM@CNT concentration increases from 15wt% to 25wt%, the sensitivity of the sensor increases from 1.55kPa -1 Increased to 3.214 kPa -1 (0~5kPa). Then the static initial capacitance of the capacitive sensor with different LM@CNT addition contents was compared with the corresponding sensitivity, such as Figure 4 As shown in (f) in the figure. As the amount of LM@CNT added increases, the capacitance value increases significantly. The initial capacitance of the capacitive sensor without LM@CNT is 2.93pF. When the amount of LM@CNT added increases from 5wt% to 25wt%, the initial capacitance increases from 22.1pF to 61.6pF, and the sensitivity of the sensor also increases from 0.19kPa -1Increased to 3.214 kPa -1 , and the changing trends are basically the same.
[0068] like Figure 5 As shown in (a), the dynamic response of the sensor under cyclic loading and unloading pressures of 20, 40, 60 and 100 kPa is shown. The relative capacitance change of the sensor changes regularly with pressure loading and unloading, showing good stability. Figure 5 As shown in (b), the sensor can maintain a stable output synchronized with the load change. The experimental results show that the prepared sensor has good stability and high resolution in a wide pressure range. Figure 5 (c) in the figure shows the hysteresis of the sensor measured from multiple loading / unloading processes. It can be seen that the designed sensor exhibits a certain degree of hysteresis, the capacitance during unloading is slightly larger than that during loading, and the maximum hysteresis is about 2.8%. This is mainly due to the viscoelasticity of the TPU material and the weak adhesion between the dielectric layer and the electrode. On this basis, in order to test the detection limit of the sensor, a piece of paper with a size of about 1.5cm*1.5cm was placed on the surface of the sensor with a pressure of about 25Pa. The loading / unloading response of the sensor to this tiny pressure is shown in Figure 2. Figure 5 As shown in (d), the response time and relaxation time are 20ms and 22ms respectively. Due to the limitations of the signal acquisition system, the dynamic response and relaxation time may even be lower than the measured value, because the signal acquisition system limits the measured value to 20ms. This experiment shows that the sensor can successfully and quickly sense a small pressure change of 25Pa in less than 20 milliseconds. In order to further study the stability of the sensor, the sensor was subjected to 3000 loading / unloading cycle tests at a cyclic pressure of 5kPa. Figure 5 As shown in (e) in the figure. The partially enlarged image shows the capacitance change curves at different cycles. There is no significant difference or drift in the relative capacitance change, indicating that the sensor has good cycle stability. Figure 5 As shown in (f) in the figure, the sensor with the electrospun fiber film as the dielectric layer is compared with other sensors in the prior art in terms of maximum sensitivity and its maintained pressure detection range. Compared with the disclosed electrospun dielectric layer sensor, the sensor of the present invention shows higher sensitivity in a wider pressure range. The above results show that the sensor developed by the present invention has high robustness and good long-term stability, and can meet the requirements of practical applications.
[0069] like Figure 6 As shown in (a) and (b) in the figure, dynamic response signals are captured during activities such as biceps brachii movement and finger clicking on the mouse. Figure 6As shown in (c) in the figure, the sensor is fixed to the throat of the volunteer with medical tape. The change of local pressure caused by the vibration of the vocal cords can be converted into a capacitance signal by using a test instrument. The measured capacitance signal is processed and converted into a Gram diagram, as shown in Figure 6 As shown in (d) in the figure, a neural network is finally used to analyze the results. Figure 6 (e) in the figure shows the response waveforms of the pressure sensor for six words, including congratulation, consistent, contact, where, are, and you. The inconsistency of the waveforms indicates that the capacitance change caused by the pressure change caused by the vocal cord vibration changes with the change of different words. Figure 6 (e) and (f) in the figure respectively show the prediction of the accuracy of the sensor of the present invention in response to different words, which can prove that the sensor of the present invention has high response capability and resolution at low detection pressure, i.e., small vibration feedback.
[0070] Reference Figure 7 , which compared the static conditions of CNT and CNT@LM after being evenly dispersed in THF / DMF solvents, and observed the stratification phenomenon in the solution containing LM@CNT, which further proved that the present invention successfully combined LM and CNT and did not separate after dispersion. The present invention is not only simple and efficient in preparation method, but also green and environmentally friendly, and has promotion value. The composite material prepared according to the present invention can be further applied to wearable devices, thermal conductive materials, electromagnetic shielding and other fields.
[0071] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0072] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a nanofiber film of LM and carbon nanotube composite filler, characterized in that: The following steps are involved: S1. Weigh the raw materials THF, DMF, TPU, LM, CNT, and PEDOT:PSS, mix THF and DMF in a ratio of 1:1 to form a base solvent, and grind LM and CNT to prepare LM@CNT filler; S2, the base solvent is divided into two parts, A and B, in a ratio of 6:4; the A part is used to dissolve TPU to prepare a component A solution, and the B part is added with the LM@CNT filler and the PEDOT:PSS, and is subjected to ultrasonic and mechanical stirring to prepare a component B solution; S3. Slowly drop the B component solution into the A component solution under stirring, and continue stirring to allow the various components to fully mix and react to form a LM@CNT / PEDOT:PSS / TPU spinning solution with uniform composition, stable performance and suitable for spinning; S4. Prepare a LM@CNT / PEDOT:PSS / TPU nanofiber film by electrospinning the LM@CNT / PEDOT:PSS / TPU spinning solution.
2. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 1, characterized in that: In step S1, the usage ratio of TPU:THF:DMF:CNT:LM:PEDOT:PSS solution is (2-2.5) g:(5-7) mL:(5-7) mL:(10-11) mg:(0.1-0.3) g:(0.05-0.15) g.
3. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 2, characterized in that: In step S1, the preparation process of the LM@CNT filler is specifically as follows: 0.1-0.3 g of LM is added to 10-11 mg of carbon nanotubes CNT, and ground for 0.5-1 h until the mixture is uniformly mixed and the grinding particle size is 5-20 um, thereby obtaining the LM@CNT filler.
4. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 1, characterized in that: In step S2, the preparation process of the component A solution is specifically as follows: 6 to 8.5 ml of the base solvent A is added to a reagent bottle, then 2 to 2.5 g of TPU is added to the reagent bottle, and the reagent bottle is placed on a heating table and gradually heated to 55 to 65° C., then heated for 0.45 to 1 hour until it is evenly dispersed, and finally the mixture is cooled to room temperature 24 to 28° C. and there are no bubbles in the bottle to obtain the component A solution.
5. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 4, characterized in that: In step S2, the preparation process of the component B solution is specifically as follows: 0.3-0.7 g of LM@CNT and 0.05-0.15 g of PEDOT:PSS are added to 4-5.5 ml of the component B base solvent, and then mechanically stirred at a speed of 20-30 rpm for 3-6 minutes in a water bath at 24-28°C and 60 Hz supermagnetic dispersion to obtain a component B solution.
6. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 1, characterized in that: In step S3, the preparation process of the LM@CNT / PEDOT:PSS / TPU spinning solution is specifically as follows: a reagent bottle containing the component A solution is clamped on a magnetic stirrer to rotate the TPU mixed solution at a speed of 600 to 800 r / min, and then the component B solution is added dropwise to the component A solution and mechanically stirred at a speed of 1000 to 1200 rpm for 30 to 60 minutes to obtain the LM@CNT / PEDOT:PSS / TPU spinning solution.
7. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 1, characterized in that: In step S4, the preparation process of the LM@CNT / PEDOT:PSS / TPU nanofiber film is specifically as follows: the LM@CNT / PEDOT:PSS / TPU spinning solution is loaded into an electrospinning device, and spinning is performed at a feed rate of 4-5 mL / h at a voltage of 15-20 kV; then a rotating drum with a surface covered with aluminum foil and a speed control function is used as a collector, and its speed is set to 200-300 r / min, and a negative voltage of 1 kV is connected to the collector; at the same time, the distance between the spinning needle and the collector is maintained at 10-15 cm; after a spinning process of 4-7 hours, the nanocomposite fiber is gradually deposited on the aluminum foil, and finally the LM@CNT / PEDOT:PSS / TPU nanofiber film is formed.
8. The method for preparing a nanofiber film of LM and carbon nanotube composite filler according to claim 7, characterized in that: The dielectric constant of the LM@CNT / PEDOT:PSS / TPU nanofiber film is 8.63-24.8, the tensile strength is 2.19-3.42 MPa, and the elongation at break is 152.6%-279.6%.
9. A LM@CNT / PEDOT:PSS / TPU nanofiber film prepared according to the method for preparing a nanofiber film of LM and carbon nanotube composite filler according to any one of claims 1 to 8.
10. An application of the LM@CNT / PEDOT:PSS / TPU nanofiber film as claimed in claim 9 in a flexible sensor, characterized in that: The capacitive sensor prepared by the LM@CNT / PEDOT:PSS / TPU nanofiber film maintains GF=1.07-3.214 in the pressure range of 0.1-20 KPa, and the response time is 20-22 ms; the sensitive performance maintains stable output after 3000 cycles.
Citation Information
Patent Citations
Atmospheric water collection nanofiber membrane with sandwich structure and preparation method thereof
CN117183505A
Preparation method of multifunctional dressing integrating photo-thermal treatment, antibiosis and temperature and humidity sensing
CN118267507A
Stretchable flexible conductive film and preparation method and application thereof
CN118581726A